HUBUNGAN ANTARA KADAR LIPID DARAH DENGAN DERAJAT HERNIASI DISKUS INTERVERTEBRALIS - Elsa Ana Purika; Susi Aulina; Audry Devisanty Wuysang; Andi Alfian Zainuddin (NEURONA, 2019)
THE CORRELATION BETWEEN SERUM LIPID LEVELS WITH THE SEVERITY OF INTER-VERTEBRAL DISC HERNIATIONABSTRACTIntroduction: Inter-vertebral Disc Herniation (IDH) is one of the common causes of low back pain (LBP). High level of blood lipids is a risk factor for atherosclerosis, and responsible as the cause of decreased blood supply to the intervertebral discs which basically has minimal vascularization, thus, it is estimated that there is a relationship between blood lipid levels and IDH.Aim: To identify the correlation between serum lipid levels with the severity of IDH.Methods: Clinical trials with cross sectional designs were carried out on subjects with IDH during April to June 2018 in Dr. Wahidin Sudirohusodo Hospital, Makassar. Serum lipid levels (HDL, LDL, triglyceride and total cholesterol) were examined and the degree of disc herniation (1 to 4) was assessed. Data analyzed using the Spearman correlation test.Results: In this study there were 40 subjects, 15 males and 25 females, with mean age 50.75 (30-62) years old. Most patients were found with degrees of IDH 2 and 3 (total 75%). The Spearman correlation test showed that there was a negative correlation between HDL with degrees of IDH, as well as a positive correlation between LDL and triglycerides with degrees of IDH, but there was no correlation between total cholesterol levels with degrees of IDH.Discussion: The lower the HDL level, the higher the degree of IDH. On the other hand, the higher the level of LDL and triglycerides, the higher the degree of IDH.Keywords: Inter-vertebral disc herniation, low back pain, serum lipid levelsABSTRAKPendahuluan: Herniasi diskus intervertebralis (HDI) merupakan salah satu penyebab nyeri punggung bawah (LBP) yang cukup sering terjadi. Tingginya kadar lipid darah merupakan faktor risiko untuk aterosklerosis, dan bertanggung jawab sebagai penyebab menurunnya suplai darah pada diskus intervertebralis yang pada dasarnya sudah minim vaskularisasi, sehingga diperkirakan terdapat hubungan antara kadar lipid darah dengan penyakit degenerasi diskus intervertebralis.Tujuan: Mengetahui hubungan antara kadar lipid darah dengan derajat herniasi diskus intervertebralis.Metode: Penelitian potong lintang terhadap subjek dengan herniasi diskus intervertebralis yang berobat ke RSUP Dr. Wahidin Sudirohusodo, Makassar, selama bulan April-Juni 2018. Dilakukan penilaian kadar lipid darah (HDL, LDL, trigiliserida, dan kolesterol total) serta derajat herniasi diskus intervertebralis (1 sampai 4) berdasarkan gejala klinis dan gambaran MRI. Analisis data menggunakan uji korelasi Spearman.Hasil: Didapatkan 40 subjek yang terdiri atas 15 orang laki-laki dan 25 orang perempuan dengan rerata usia 50,75 (30–62) tahun. Mayoritas subjek mengalami HDI derajat 2 dan 3 (total 75%). Uji korelasi Spearman menunjukkan adanya korelasi negatif antara kadar HDL dengan derajat HDI, serta korelasi positif antara kadar LDL dan trigliserida dengan derajat HDI, namun tidak terdapat korelasi antara kadar kolesterol total dengan derajat HDI.Diskusi: Semakin rendah kadar HDL, maka semakin berat derajat HDI. Sebaliknya semakin tinggi kadar LDL dan trigliserida, maka semakin berat derajat HDI.Kata kunci: Herniasi diskus intervertebralis, kadar lipid darah, nyeri punggung bawah